OpenGL® Shading Language, Second Edition - Rost, Randi (Addison-Wesley Professional, 2006)
"As the 'Red Book' is known to be the gold standard for OpenGL, the 'Orange Book' is considered to be the gold standard for the OpenGL Shading Language. With Randi's extensive knowledge of OpenGL and GLSL, you can be assured you will be learning from a graphics industry veteran. Within the pages of the second edition you can find topics from beginning shader development to advanced topics such as the spherical harmonic lighting model and more." --David Tommeraasen, CEO/Programmer, Plasma Software "This will be the definitive guide for OpenGL shaders; no other book goes into this detail. Rost has done an excellent job at setting the stage for shader development, what the purpose is, how to do it, and how it all fits together. The book includes great examples and details, and good additional coverage of 2.0 changes!" --Jeffery Galinovsky, Director of Emerging Market Platform Development, Intel Corporation "The coverage in this new edition of the book is pitched just right to help many new shader-writers get started, but with enough deep information for the 'old hands.'" --Marc Olano, Assistant Professor, University of Maryland "This is a really great book on GLSL--well written and organized, very accessible, and with good real-world examples and sample code. The topics flow naturally and easily, explanatory code fragments are inserted in very logical places to illustrate concepts, and all in all, this book makes an excellent tutorial as well as a reference." --John Carey, Chief Technology Officer, C.O.R.E. Feature Animation OpenGL® Shading Language, Second Edition , extensively updated for OpenGL 2.0, is the experienced application programmer's guide to writing shaders. Part reference, part tutorial, this book thoroughly explains the shift from fixed-functionality graphics hardware to the new era of programmable graphics hardware and the additions to the OpenGL API that support this programmability. With OpenGL and shaders written in the OpenGL Shading Language, applications can perform better, achieving stunning graphics effects by using the capabilities of both the visual processing unit and the central processing unit. In this book, you will find a detailed introduction to the OpenGL Shading Language (GLSL) and the new OpenGL function calls that support it. The text begins by describing the syntax and semantics of this high-level programming language. Once this foundation has been established, the book explores the creation and manipulation of sha...